Fabrication and Evaluation of Large Area Mo/Si Soft X-Ray Multilayer Mirrors at Indus SR Facilities. (15th August 2012) - Rao, P. N.; Nayak, Maheswar; Lodha, G. S.; Rai, S. K.; Srivastava, A. K.; Modi, M. H.; Sagdeo, A.
Abstract : Large area Mo/Si multilayer (ML) mirrors with high reflectivity are fabricated using magnetron sputtering deposition system. Thin film growth is optimized for film roughness, density, and interface quality by changing process parameters through fabrication of thin films. Mo/Si MLs are fabricated with varying thickness ratio, number of layer pairs, and periodicity from 0.3 to 0.45, 5 to 65, and 40 to 100 Å, respectively. The samples are characterized using hard X-ray reflectivity and transmission electron microscopy. Soft X-ray performance tests of MLs are done by soft X-ray reflectivity using Indus-1 synchrotron radiation. ML coating with thickness errors of ~ 0.03% per layer and interface roughness in the range of 2 to 5 Å has been realized. The lateral variation of the periodicity is controlled within 0.5 Å over the300 × 100  mm 2 area of the plane substrate by using substrate motion and appropriate masking arrangement. Maximum variation of periodicity from run to run is less than 0.5 Å. Peak reflectivity of ~ 63% at wavelength of ~ 127 Å is achieved for incident angle of 71 degree.